Temporal Sequence of Comorbid Alcohol Use Disorder and Anorexia Nervosa - Baker, Jessica H. (2012)
Women with eating disorders have a significantly higher prevalence of substance use disorders than the general population. The goal of the current study was to assess the temporal pattern of comorbid anorexia nervosa (AN) and alcohol use disorder (AUD) and the impact this ordering has on symptomatology and associated features. Women were placed into one of three groups based on the presence or absence of comorbid AUD and the order of AN and AUD onset in those with both disorders: (1) AN Only, (2) AN First, and (3) AUD First. The groups were compared on psychological symptoms and personality characteristics often associated with AN, AUD, or both using general linear models. Twenty-one percent of women (n = 161) with AN reported a history of AUD with 115 reporting AN onset first and 35 reporting AUD onset first. Women with binge-eating and/or purging type AN were significantly more likely to have AUD. In general, differences were found only between women with AN Only and women with AN and AUD regardless of order of emergence. Women with AN and AUD had higher impulsivity scores and higher prevalence of depression and borderline personality disorder than women with AN Only. Women with AN First scored higher on traits commonly associated with AN, whereas women with comorbid AN and AUD displayed elevations in traits more commonly associated with AUD. Results do not indicate a distinct pattern of symptomatology in comorbid AN and AUD based on the temporal sequence of the disorders.